2004
DOI: 10.1203/01.pdr.0000099776.66136.39
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins in Otitis-Prone Children

Abstract: Defective or immature antibody responses to pathogens in children may explain the increased susceptibility to acute otitis media (AOM) in otitis-prone children. In literature, data on immunology have been based on studies of small groups of severely otitis-prone children and have not been consistent. Humoral immune status was assessed in 365 children, 1-7 years old, with two or more documented episodes of AOM in the previous year. Children with 4 or more episodes in the preceding year were defined as otitis-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
(16 reference statements)
1
31
2
Order By: Relevance
“…The immune response to pathogens develops rapidly during the first few years of life, as children become exposed to an increasing number of microbial species and strains. The high incidence and high rate of spontaneous recovery from OM suggests that recovery is a natural phenomenon and part of the gradual maturation of the child's immune system, though a defective or immature antibody response to OM pathogens may explain the increased susceptibility of some children to OM (36). Differences in the presence/absence and levels of pathogenspecific IgG and IgM at particular body sites may be one of the mechanisms by which OM pathogens are able to facilitate the development of OM disease.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to pathogens develops rapidly during the first few years of life, as children become exposed to an increasing number of microbial species and strains. The high incidence and high rate of spontaneous recovery from OM suggests that recovery is a natural phenomenon and part of the gradual maturation of the child's immune system, though a defective or immature antibody response to OM pathogens may explain the increased susceptibility of some children to OM (36). Differences in the presence/absence and levels of pathogenspecific IgG and IgM at particular body sites may be one of the mechanisms by which OM pathogens are able to facilitate the development of OM disease.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is more severe in patients with a defect in polysaccharide antibody production associated with IgG subclass deficiency and SIgAD [42][43][44]. IgG2 may protect against polysaccharides, because it has been indicated that patients with low IgG2 had recurrent episodes of otitis media despite exhibiting normal levels of IgA, IgM, IgG and IgG1 [45]. Sinopulmonary complications such as otitis media are more common in PAD than in combined immunodeficiency …”
Section: Otitis Mediamentioning
confidence: 99%
“…Serum concentrations of Igs in patients with recurrent otitis media were lower than in a general control group or in patients with non-recurrent otitis media, with some of these differences being significant (14,28). We did not correct concentrations according to age and gender, but our results could not confirm findings showing that Ig concentrations in serum and exudates had clinical significance in patients with recurrent otitis media (29).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, several studies have shown that children with low serum immunoglobulin (Ig) A, IgG, and IgM concentrations during the initial stages of otitis media have a higher incidence of recurrent OME than those with lower serum Ig concentrations (14,15). Little is known, however, regarding the association between recurrence and the concentrations of immunoglobulin in the middle ear cavity.…”
Section: Introductionmentioning
confidence: 99%